2022
DOI: 10.3389/fnut.2022.889131
|View full text |Cite
|
Sign up to set email alerts
|

Reno-Protective Effect of Low Protein Diet Supplemented With α-Ketoacid Through Gut Microbiota and Fecal Metabolism in 5/6 Nephrectomized Mice

Abstract: BackgroundLow protein supplemented with α-ketoacid diet (LKD) was recommended to be an essential intervention to delay the progression of chronic kidney disease (CKD) in patients who were not yet on dialysis. Aberrant gut microbiota and metabolism have been reported to be highly associated with CKD. However, the effect of LKD on gut microbiota and related fecal metabolism in CKD remains unclear.MethodsMice were fed with normal protein diet (NPD group), low protein diet (LPD group), and low protein diet supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Te F/B ratio is usually used as a marker refecting the condition of gut microbiota [44]. In our research, Firmicutes showed an upward trend in feces of CKD rats, while Bacteroidetes showed a downward trend, and the ratio of Firmicutes to Bacteroidetes (F/B) increased, which was consistent with previous reports [45]. After RBP treatment, the proportion of Firmicutes at the phylum level was reduced and the proportion of Bacteroidetes and F/B was increased, suggesting that RBPs could act by regulating the proportion of the microbiota.…”
Section: Discussionsupporting
confidence: 92%
“…Te F/B ratio is usually used as a marker refecting the condition of gut microbiota [44]. In our research, Firmicutes showed an upward trend in feces of CKD rats, while Bacteroidetes showed a downward trend, and the ratio of Firmicutes to Bacteroidetes (F/B) increased, which was consistent with previous reports [45]. After RBP treatment, the proportion of Firmicutes at the phylum level was reduced and the proportion of Bacteroidetes and F/B was increased, suggesting that RBPs could act by regulating the proportion of the microbiota.…”
Section: Discussionsupporting
confidence: 92%
“…Family Lachnospiraceae isa critical member of GM. Previous studies demonstrated that Lachnospiraceae took an essential part in the pathogenesis of CKD (43,44), however, there were conflicting findings among these studies. Lai et al (45) found that the abundance of Lachnospiraceae was increased in mice with kidney damage and in patients with CKD, which might predict that it was a risk bacterial taxon for CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Another species, Parabacteroides sp. CT06, which belongs to the Tannerellaceae family, is linked to the α-ketoacid diet [70].…”
Section: Discussionmentioning
confidence: 99%